Agreement and illusion of disagreement: An ERP study on Basque. (July 2019) - Mancini, Simona; Massol, Stephanie; Duñabeitia, Jon A.; Carreiras, Manuel; Molinaro, Nicola
Abstract: Agreement is a syntactic relation involving a controller (e.g., a noun) and a target with matching inflectional morphology (e.g., a verb). Across languages, electrophysiological studies consistently report that the presence of a mismatch yields late positive effects (P600), often preceded by early negativities. The current study focuses on person agreement in Basque to investigate whether online processing routines are modulated by the relative semantic prominence of nominal and verbal person features. In an event-related potentials experiment in Basque, we manipulated the semantic markedness of nominal and verbal person features, creating 1st (marked) and 3rd (unmarked) person correct and incorrect sentences [ Japoniarrok 1pl euskara ikasi dugu 1pl /*dute 3pl gustora (We Japanese have1pl/*3pl learn Basque with pleasure); Japoniarrek 3pl euskara ikasi dute 3pl /*dugu1pl gustora (The Japanese have3pl/*1pl learnt Basque with pleasure)]. Both mismatches elicited an N400 effect, but only marked 1st person mismatches (Japoniarrok1pl … *dute3.pl ) generated a P600, suggesting that (i) mismatches with unmarked 3rd person subjects ( Japoniarrek 3.pl … *dugu 1.pl ) are not treated as outright violations; (ii) the emergence of late positive effects is sensitive to fine-grained discourse information. Overall, these results call for a revision in the analysis of agreement relations from a theoretical and a processing perspective.